2018
DOI: 10.21014/acta_imeko.v7i2.539
|View full text |Cite
|
Sign up to set email alerts
|

ISME activity on the use of Autonomous Surface and Underwater Vehicles for acoustic surveys at sea

Abstract: <p class="Abstract"><span lang="EN-US">The paper presents an overview of the recent and ongoing research activities of the Italian Interuniversity Center on Integrated Systems for the Marine Environment (ISME) in the field of geotechnical seismic surveying. Such activities, performed in the framework of the H2020 European project WiMUST, include the development of technologies and algorithms for Autonomous Surface Crafts and Autonomous Underwater Vehicles to perform geotechnical seismic surveying b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The final experiment consisted of a 2 h and 15 min long survey in the open sea, covering an area of approximately 100 ×200 m just outside the Sines harbor. The fleet of robots that was employed in the experiment was the following one: DELFIM (ASV) (Alves et al, 2006), acting as a formation leader, carrying a sparker, and acting as a navigation anchor, performing CPF with ULISSE. ULISSE (ASV) (Antonelli et al, 2018), carrying a sparker and performing CPF with DELFIM. MBLACK (Medusa ASV Abreu, Botelho, et al, 2016), acting as a navigation anchor, tracking the formation leader. MRED and MYELLOW (Medusa AUVs), F1 and F2 (Folaga AUVs Alvarez et al, 2009), each of them tracking the formation leader, towing streamers, and acquiring seismic data.…”
Section: Autonomous Geotechnical Survey In Open Sea: Field Resultsmentioning
confidence: 99%
“…The final experiment consisted of a 2 h and 15 min long survey in the open sea, covering an area of approximately 100 ×200 m just outside the Sines harbor. The fleet of robots that was employed in the experiment was the following one: DELFIM (ASV) (Alves et al, 2006), acting as a formation leader, carrying a sparker, and acting as a navigation anchor, performing CPF with ULISSE. ULISSE (ASV) (Antonelli et al, 2018), carrying a sparker and performing CPF with DELFIM. MBLACK (Medusa ASV Abreu, Botelho, et al, 2016), acting as a navigation anchor, tracking the formation leader. MRED and MYELLOW (Medusa AUVs), F1 and F2 (Folaga AUVs Alvarez et al, 2009), each of them tracking the formation leader, towing streamers, and acquiring seismic data.…”
Section: Autonomous Geotechnical Survey In Open Sea: Field Resultsmentioning
confidence: 99%
“…A full survey was carried out by the WiMUST team including seven vehicles. The fleet included the ULISSE [5] and Delfim autonomous catamarans, three Medusas [1] and two Folagas [6] autonomous underwater vehicles (see Fig. 1).…”
Section: Results: the Wimust Trialsmentioning
confidence: 99%
“…Localization is one of the most important basic abilities for an autonomous vehicle to perform autonomously a wide number of tasks (Ferri et al, 2017 ; Simetti et al, 2017 ; Antonelli et al, 2018 ), so that an accurate and reliable localization algorithm is a key practical tool for the success of mission in many applications of underwater robotics.…”
Section: Introductionmentioning
confidence: 99%
“…The research activity reported in this paper stems from the above considerations and is strongly inspired by the experience gained within a European project (Antonelli et al, 2018 ). The goal is to extend the preliminary results achieved by the same authors in De Palma et al ( 2015 ) and De Palma et al ( 2019 ) as follows.…”
Section: Introductionmentioning
confidence: 99%